2023
DOI: 10.3390/biomedicines11051335
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Metabolism Failure as a Risk Factor for Postoperative Complications after Aortic Prosthetics

Abstract: Postoperative complications in cardiovascular surgery remain an important unresolved problem, in particular in patients with aortic aneurysm. The role of the altered microbiota in such patients is of great interest. The aim of this pilot study was to determine whether the development of postoperative complications in patients with aortic aneurysm is related with initial or acquired disorders of microbiota metabolism by monitoring the level of some aromatic microbial metabolites (AMMs) circulating in the blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…p-HPhLA is described as having prognostic significance in cases of infectious complications and sepsis; its values can increase ten-fold. [14]. Meta-analysis showed that the risk of death was 1.5 times higher in patients experiencing severe postoperative complications (Clavien-Dindo ≥ III) than in patients without severe complications [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p-HPhLA is described as having prognostic significance in cases of infectious complications and sepsis; its values can increase ten-fold. [14]. Meta-analysis showed that the risk of death was 1.5 times higher in patients experiencing severe postoperative complications (Clavien-Dindo ≥ III) than in patients without severe complications [3].…”
Section: Discussionmentioning
confidence: 99%
“…[12,13]. One of the promising markers for monitoring infectious complications in surgical patients, reflecting microbiota dysfunction, could be aromatic microbial metabolites, but their role in cancer has not been studied [14,15].…”
Section: Introductionmentioning
confidence: 99%